IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 11-017/PUU-I/2003 TERHADAP PERLINDUNGAN HUKUM HAK DIPILIH - Ngastawa, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Paper that had the title: "Juridical implications of the Constitutional Court Decision Number 011-017/PUU-I/2003 on the Legal Protection for the Rights to be Eelected." This explores two issues: 1) how the legal protection of the settings selected in the state system of Indonesia ; 2) what are juridical implications of the Constitutional Court Decision Number 011-017/PUU-I/2003 on the legal protection for the rights to be elected. To solve both problems, this paper uses normative legal research methods. Approach being used is the statute approach, case approach, and a conceptual approach. Further legal materials collected were identified and analyzed using descriptive analysis techniques. Legal protection for the right to be elected in the state system of Indonesia can be traced from the 1945 opening, the articles in the body of the 1945 Constitution, Article 27 paragraph (1), Article 28D (1) and paragraph (3) and Article 28 paragraph (3) 1945 Second Amendment, MPR Decree Number XVII/MPR/1998, Article 43 of Law Number 39 of 1999, Article 21 of the Universal Declaration of Human Rights, and Article 25 of the International Covenant  on Civil and Political Rights. Discussion of the juridical implications of the Constitutional Court Decision Number 011-017/PUU-I/2003 on the legal protection for the rights to be elected have been included: a) only on the juridical implications of representative institutions no longer marked with specified requirements as stipulated in Article 60 letter g of Law Number 12 Year 2003 in Law Number 10 Year 2008; b) juridical implications of the political field for the right to be elected is the absence of any discriminatory treatment in legislative product formed by the House of Representatives and the President as well as products of other legislation forward.
Keywords: Juridical Implications of the Constitutional Court Decision Number 011-017/PUU- I/2003; Legal Protection; the Rights to be Elected